سعاده, - سعاده سليم; شتيوي عبدالمالك (University of Eloued جامعة الوادي, 2024)
هدفت الدراسة الحالية الى معرفة مستوى الذكاء الاجتماعي لدى طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية ، وتحديد ما اذا كان هناك فروق في مستوى الذكاء الاجتماعي بين طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية بسكرة حسب المستوى الدراسي ، وكذا معرفة ما اذا كان هناك فروق في مستوى الذكاء الاجتماعي بين طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية وطلبة الكليات الأخرى ، ولهذا الغرض استخدام الباحثان المنهج الوصفي على عينة متكونة من (420) طالبا وطالبة تم اختيارهم بطريقة العينة الحصصية العشوائية ، واستخدم مقياس الذكاء الاجتماعي للسيد أبو هاشم (2008)، وتمت معالجة البیانات احصائیا باستخدام برنامج 25 spss وأظهرت النتائج أن مستوى الذكاء الاجتماعي لدى طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية مرتفع ،كما أظهرت أيضا وجود فروق دالة احصائيا في مستوى الذكاء الاجتماعي لدى طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية حسب المستوى الدراسي، في حين أنه لا توجد فروق دالة احصائيا في مستوى الذكاء الاجتماعي بين طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية وطلبة التخصصات الأخرى.Abstract: the aim of the current study was to determine the level of social intelligence among students of the Institute of Sciences and Technologies of Physical and Sports Activities, and to identify whether there are differences in social intelligence levels between students of the Institute of Sciences and Technologies of Physical and Sports Activities based on their academic level. Additionally, the study aimed to determine whether there are differences in social intelligence levels between students of the Institute of Sciences and Technologies of Physical and Sports Activities and students of other majors. For this purpose, the researchers used a descriptive methodology on a sample of 420 male and female students who were selected using random sampling. The researchers used the Social Intelligence Scale by Mr. Abu Hashem (2008), and the data was statistically analyzed using SPSS version 25. The results showed that the level of social intelligence among students of the Institute of Sciences and Technologies of Physical and Sports Activities is high. Additionally, statistically significant differences were found in the level of social intelligence among students of the students of the Institute of Sciences and Technologies of Physical and Sports Activities based on their academic level, while there were no statistically significant differences in the level of social intelligence between students of the students of the Institute of Sciences and Technologies of Physical and Sports Activities and students of other majors.
Keywords: Social Intelligence; University Students; Students of the Institute